Cover Picture: Palladium‐Catalyzed Divergent Arylation with Triazolopyridines: One‐Pot Synthesis of 6‐Aryl‐2‐α‐styrylpyridines (Adv. Synth. Catal. 6/2016). Issue 6 (7th March 2016) - Moon, Youngtaek; Kwon, Soonhyung; Kang, Dahye; Im, Honggu; Hong, Sungwoo
Abstract : The cover picture, provided by Sungwoo Hong and co‐workers, illustrates a new strategy for palladium‐catalyzed arylation reactions with triazolopyridines, wherein two different chemical transformations (at positions C‐3 and C‐7) are selectively observed by differentiating substrates using different bases. Moreover, two different catalytic arylation events were successfully performed in a one‐pot sequence, providing a convenient access to 6‐aryl‐2‐α‐styrylpyridines of high synthetic utility. Details can be found in the full paper on pages 958–964 (Y. Moon, S. Kwon, D. Kang, H. Im, S. Hong, Adv. Synth. Catal. 2016, 358, 958–964; DOI:10.1002/adsc.201500967 ).